Global Population Trends Challenges Facing World Leaders - Population Reference Bureau, Inc., Washington, DC.; Scommegna, Paola; Population Reference Bureau, Inc., Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
This pamphlet explores the dynamics of world population, highlighting steps world leaders can take to address population problems and improve the lives of people worldwide. With jet-age transportation and electronic communication, economic and social interdependence of nations is greater than ever before and is likely to increase in the future. Politically, the most sensitive area is migration, particularly for low-growth areas close to high-growth areas: Europe's proximity to North Africa and the Middle East, and the United States proximity to the Caribbean Basin countries. Trade and financial relationships also channel the effects of internal population pressures across international borders. The response to population growth between now and the time population stabilization occurs will shape the world that future generations will share. (SM)
Sponsoring Agency: Rockefeller Foundation, New York, NY.
Sponsoring Agency: Agency for International Development (IDCA), Washington, DC.
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Geographic Distribution; Migration; Population Distribution; Population Trends; Social Sciences; World Problems; Population Control -- Population Information; Global Survival; Reports, Research